2015
DOI: 10.1007/s00411-015-0585-6
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome aberrations in workers with exposure to α-particle radiation from internal deposits of plutonium: expectations from in vitro studies and comparisons with workers with predominantly external γ-radiation exposure

Abstract: mFISH analysis of chromosome aberration profiles of 47 and 144 h lymphocyte cultures following exposure to 193 mGy α-particle radiation confirmed that the frequency of stable aberrant cells and stable cells carrying translocations remains constant through repeated cell divisions. Age-specific rates and in vitro dose-response curves were used to derive expected translocation yields in nine workers from the Mayak nuclear facility in Russia. Five had external exposure to γ-radiation, two of whom also had exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
4
5
0
Order By: Relevance
“…However, insertions are now being resolved as being part of much larger, mostly, unstable complex rearrangements when visualised by M-FISH ( Figure 2), in keeping with those previously described, meaning the potential transmissibility of these insertions is much lower than previously thought [43,57]. This is reflected by the low relative proportion of complex aberrations which are classified as being of the transmissible-type and the low estimated frequency of damaged, but stable cells [76][77][78]. Accordingly, insertions are characteristic features of both stable and unstable complex aberrations induced after exposure to high-LET radiation.…”
Section: Chromosome Insertions As Stable Indicators Of High-let Radiasupporting
confidence: 80%
See 1 more Smart Citation
“…However, insertions are now being resolved as being part of much larger, mostly, unstable complex rearrangements when visualised by M-FISH ( Figure 2), in keeping with those previously described, meaning the potential transmissibility of these insertions is much lower than previously thought [43,57]. This is reflected by the low relative proportion of complex aberrations which are classified as being of the transmissible-type and the low estimated frequency of damaged, but stable cells [76][77][78]. Accordingly, insertions are characteristic features of both stable and unstable complex aberrations induced after exposure to high-LET radiation.…”
Section: Chromosome Insertions As Stable Indicators Of High-let Radiasupporting
confidence: 80%
“…The biological reason for this long-term survival of such heavily damaged PBLs is unclear. However, similar observations, at varying frequencies, have been reported elsewhere including in plutonium workers [87][88][89][90], thorotrast patients [85,91], veterans of nuclear testing [92], A-bomb survivors [93], astronauts and patients receiving carbon therapy [81]. Interestingly, Hande et al [79] found a significant correlation with estimated plutonium dose to the bone marrow (from ~500mGy) and yield of complex aberrations suggesting quantification could potentially be used for dose reconstruction.…”
Section: Complexity Per Se As An Indicator Of High-let Radiationsupporting
confidence: 65%
“…The remaining non-transmissible complexes are proposed to represent mature T-cells which remain in their 1 st interphase for months or even years after irradiation, until sampled and artificially stimulated to divide in culture. The biological mechanism for this long-term persistence of such heavily damaged PBLs is unclear however similar observations have been reported elsewhere [ 24 , 49 , 50 ]. Thus, complex chromosome exchanges, irrespective of their stability through cell division, are reliable and useful indicators of chronic α-particle exposure.…”
Section: Discussionsupporting
confidence: 68%
“…On completion of the study, individual dosimetry records were re-examined to confirm external doses and determine the extent of any internal alpha-particle dose. Only those with internal alpha-particle doses ,10 mGy were included, this being recognized from previous in vitro (28) and in vivo studies (29) as likely to result in ,0.5 translocations per 1,000 cells. The current study population of 164 comprised 12 control individuals with cumulative external doses ,50 mGy, 63 with doses 50-249 mGy, 65 with doses 250-499 mGy and 24 with doses .500 mGy.…”
Section: Current Study Populationmentioning
confidence: 99%